(untitled) (Circe de clásicos y modernos, 2022)
This paper explores aspects of what I shall call pity or compassion in Homer (especially Iliad 24) and Aristotle (especially the Rhetoric), but nothing very much hangs on the precise terminology. The phenomena covered by terms such as “compassion”, “sympathy”, “empathy”, and “pity” (and their analogues, where they exist, in other languages) constitute a family in which resemblances are often really rather close in practice (even if particular members of the group pass in and out of fashion and take on a range of different connotations at different periods and in different contexts). In concentrating on the theory and practice of literature, I am not offering a synthetic account of ancient Greek pity; instead I focus, in the main, on just two authors, Homer and Aristotle, and proceed primarily by means of a confrontation between the representation of pity in the final book of the Iliad and the theorization of that emotion in Aristotle’s Rhetoric and Poetics. I begin with Homer, but immediately bring the Homeric narrative into relation with Aristotle’s account of pity in the Rhetoric. This will lead to some thoughts on the nature of pity and compassion in Homer in general, before we return to the contrast between Homer and Aristotle (with emphasis on the Poetics), a contrast that is in some ways underscored by certain differences between Aristotle and Plato on the emotional effects of epic and tragic poetry. A particular focus will be Aristotle’s linkage of pity with the kind of thing that one would fear were it likely to happen to oneself, by contrast with the connection in Homer and Plato between pity for others and the experience of grief, both one’s own and that of others.